Gigantic Macromastia: Modified Superomedial Pedicle is a Good Solution - James Roy Kanjoor; Aakansh Jain; Sathya Pakkiri (Indian Journal of Plastic Surgery)
Background Reduction of very huge breast—gigantic macromastia—is a challenge to breast surgeons in choosing the right procedure to obtain an optimal outcome. The feasibility of a superomedial pedicle (SMP) with some modifications proves to be a good option to achieve a viable nipple areolar complex (NAC) with good size and shape after good resection above 800 g.